2019
DOI: 10.1101/842922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell lineage-dependent chiral actomyosin flows drive cellular rearrangements in early development

Abstract: Proper positioning of cells is important for many aspects of embryonic development, tissue homeostasis, and regeneration. A simple mechanism by which cell positions can be specified is via orienting the cell division axis. This axis is specified at the onset of cytokinesis, but can be reoriented as cytokinesis proceeds.Rotatory actomyosin flows have been implied in specifying and reorienting the cell division axis in certain cases, but how general such reorientation events are, and how they are controlled, rem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Changes in cell shape over time reveal the dynamics of cellular mechanical properties, including, but not limited to, the passive force due to the surrounding environment, stiffness, and adhesion 16,18 . In addition, the changing shapes of cells during development may suggest ongoing cell signal transduction, division, or migration, which are processes specifically associated with cell identity and cell fate 45,54,56 . Our membrane segmentation allows accurate delineation of cell shape dynamics throughout development with a resolution of~1.5 min.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in cell shape over time reveal the dynamics of cellular mechanical properties, including, but not limited to, the passive force due to the surrounding environment, stiffness, and adhesion 16,18 . In addition, the changing shapes of cells during development may suggest ongoing cell signal transduction, division, or migration, which are processes specifically associated with cell identity and cell fate 45,54,56 . Our membrane segmentation allows accurate delineation of cell shape dynamics throughout development with a resolution of~1.5 min.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear if the asymmetry has biological significance as the cells have equivalent lineage potential ( Wood, 1991 ), though it has been observed that ABpl and ABpr behave differently in the compressed embryo ( Jelier et al , 2016 ; Pohl and Bao, 2010 ). One possibility is that the volume difference is a consequence of geometric constraints, as the ABp spindle position is oriented by directed cortical flows ( Naganathan et al , 2014 ; Pimpale et al , 2020 ) that may be affected by the compression of the embryo for imaging, which is supported by our observation that this volume asymmetry disappeared in uncompressed embryos.…”
Section: Discussionmentioning
confidence: 57%